Destilasi Kering Sampah Plastik Low Density Polyethylene (LDPE) - Rivaldo Lee Mogot; Dewa Anom; Jenny Kumajas (Jurnal Kimia Fullerene, 2020)
Indonesia is the second largest contributor of plastic waste in the world. Lack of public knowledge about the negative effects of plastic waste and the management of plastic waste that has not been good causes a buildup of plastic waste. This study aims to convert LDPE plastic waste into a liquid similar to petroleum, separate and analyze the chemical components present in the liquid produced by the distillation of dry plastic waste. Plastic waste is dry distilled at temperatures up to 300 oC, without solvents involved. Liquid distilled from a distillation of dry distillation (Fractionation) to separate the chemical components. To find out what chemical components are present, the resulting liquid from multilevel distillation (Fractionation) was analyzed by means of Infrared Spectroscopy (IR) and Gas Chromatography-Mass Spectrometry (GC-MS). The results of IR analysis on the LDPE plastic waste fractionation distillation fluid showed the presence of Aromatic, Alkane and Alkene functional groups. The results of GC-MS analysis on the LDPE plastic waste fractionation distillation fluid for each fraction showed that in general it is a group of hydrocarbon compounds with different molecular masses.